A Survey of Different Methods in Border Security and Surveillance - Sood, Palak; Sharma, Himani; Sehra, Sumeet Kaur (International Journal of Computer Sciences and Engineering, 2019)
This paper presents a review of the existing border security and surveillance techniques proposed, keeping in view the energy optimization and economic integration at the same time. As the task of border monitoring becomes more and more difficult, searching for solutions beyond physical barriers may be one way to improve security. This paper aims to compare different researches in border security with respect to technique, technology, merits and demerits, time complexity, efficiency and unique features. This paper also highlights their fundamental working principles. The solely aim of this paper is to present a direct comparison of various major researches done in this field so as to facilitate the best optimized method to be deployed according to the current scenario.